Depressive Disorder Among Child And Adolescent Patients Attending Psychiatry OPD at Nepalgunj Medical College, Kohalpur - Adhikari, Jyoti; Belbase, Mohan; Jalan, Rekha (Journal of Nepalgunj Medical College, 2017)
BACKGROUND: Depression is one of the common psychiatric problem among child and adolescents especially during the peri pubertal stage. It is found to be more common in females than males. Poor and unhealthy family atmosphere, family dispute, broken family, parents working abroad, physical abuse are few of the causes of childhood depression. Signs and symptoms of childhood depression may present with vague and atypical physical symptoms as compared to adults. Methods: This is a descriptive study done in patients attending psychiatry OPD of Nepalgunj Medical College, Kohalpur for the period of six months from July to December 2015. Results: Out of 245 patients, 142(57.9%) patients were diagnosed as depressive disorder. Rest of the pediatric patients 103(42.1%) attending the psychiatry OPD were of seizure disorder, bipolar disorder, conversion disorder, mental retardation, adjustment disorder etc. There were 88(62%) females and 54(38%) male patients showing the majority of patients as females. The most common age group involved in the study population was 11-14 years 116(81.7%) followed by 6-10 years age group 23(16.2%) and up to 5 years 3(2.1%) respectively. Conclusion: Depression is quite common in pediatric population mostly during the peripubertal stage. It is seen most frequently in females. JNGMC Vol. 14 No. 1 July 2016, Page: 8-10